G422(P) Deep vein thrombosis and silent pulmonary emboli: diagnostic dilemmas and lessons learnt. (May 2019) - Pecqueur, J; Joseph, S; Slater, A; Babiker, A
Abstract : Background: Deep vein thrombosis (DVT) and pulmonary embolism (PE) are rare in children. Whereas risk stratification and treatment pathways are validated for adults with these conditions, their relevance to paediatric patients is uncertain. Case: A 13 year-old girl with high BMI presented with 2 days of tender, right leg swelling and intermittent fever with no rash, arthropathy, cardiac or respiratory compromise. Doppler scans revealed an extensive DVT involving the right great saphenous and external iliac veins. Initial bloods suggested an inflammatory process, with raised CRP and ESR, deranged LFTs and concomitant lymphopenia. Abdominal ultrasound demonstrated extensive fatty liver changes. Bilateral pulmonary emboli were identified on CT scan. Multispecialty collaboration enabled comprehensive risk management and further investigations for infection, malignancy and autoimmune disorders. Subsequently the patient developed an erythematous rash. Her lupus anticoagulant, antinuclear and anti-double stranded DNA antibodies tested weakly positive and she was found to be heterozygous for factor V Leiden. This enabled a diagnosis of juvenile-onset systemic lupus erythematosus (JoSLE) to be made 3 weeks after initial presentation. Discussion: Patients can be asymptomatic with PE therefore, high index of suspicion must be maintained and chest imaging considered in children with DVT. Guidelines for stratifying the risk of catastrophic respiratory events exist for adults but not children and this case raises the question of whether it would be useful to develop new guidance regarding levels of care and monitoring required for children with PE. Increased risk of thrombosis is a known association of SLE, particularly with positive antiphospholipid antibodies. The multisystem nature of SLE and its diverse presentation poses a significant diagnostic challenge. The varying chronology of symptoms highlights the need for regular review and documentation of clinical features to support diagnosis. Conclusion: Collaborative specialty team working and involvement of adult medicine colleagues, with central co-ordination of care from a general paediatrician, was essential to inform the risks for this child and enable treatment to be initiated safely, whilst ensuring effective communication with the child and family. JoSLE must be considered in children demonstrating multi-system symptoms.